Strategi Pengembangan Potensi Pariwisata sebagai Daya Tarik Wisata di Kecamatan Pulau Ende - Fitriani, Afifah; Penu, Yustina Paulina; Djata, Baltasar Taruma (JURNAL EQUILIBRIUM, 2022)
This study aims (1) to determine the strengths, weaknesses, opportunities and threats in the strategy of developing tourism potential as a tourist attraction in Pulau Ende District (2) to determine the strategy for developing tourism potential as a tourist attraction in Pulau Ende District. This study uses qualitative research methods. In order to achieve the objectives of this study, the authors use the SWOT analysis method. SWOT (Strengths, Weaknesses, Opportunities, Threats) is an analysis method of the internal factor analysis summary (IFAS), external factor analysis summary (IFAS) and the SWOT matrix. Based on the results of IFAS factor analysis and EFAS factor analysis, the following values were obtained: strengths (3.59), weaknesses (-1.85), opportunities (3.00), threats (-3.22) so that the coordinate points (1.74; -0.22) in quadrant II (Diversification Strategy), A verified strategy is a strategy that faces various threats, but this potential still has internal strength. The strategy that must be implemented is one that uses strength to take advantage of long-term opportunities by means of verified strategies. This indicates that tourism development in the Pulau Ende sub-district faces various threats from outside, although this score still has strength from an internal perspective. Specific strategies that can result from tourism development in Pulau Ende District are increasing the development of tourism strategies, improving around tourism sites, improving tourism promotion, improving and improving facilities and infrastructure for tourist attractions, improving the quality of human resources, and increasing collaboration with various sectors efforts to overcome the lack of budget shortage of funds.